Impact of DNA methylation on digestive and metabolic gene expression in red pandas (Ailurus fulgens) during the transition from milk to bamboo diet - Lei Chen; Liang Zhang; Yanni Zhao; Ming He; Honglin Wu; Jingheng Wang; Zhoulong Chen; Yongqi Zhao; Fujun Shen; Xiuyue Zhang (BMC Genomics)
Abstract Background DNA methylation plays a crucial role in species development and environmental adaptation. In mammals, there are significant dietary changes from infancy to adulthood. Notably, the red panda transitions from milk consumption as juveniles to a bamboo-based diet as adults, with significant alterations in food characteristics and nutritional content. However, the regulatory role of DNA methylation in this process remains unclear. In this study, we investigate the regulatory role of DNA methylation on the expression of digestive and metabolic genes in the liver and pancreas during the red panda’s dietary transition from suckling stage to adulthood. Results Our findings reveal significant differences in DNA methylation patterns before and after dietary transition, highlighting the specific alterations in the methylation profiles of genes involved in lipid, carbohydrate, and amino acid metabolism. We found that perilipin-4 (PLIN4) is hypomethylated and highly expressed in the liver of adult red pandas, facilitating lipid droplet formation and storage, crucial for adapting to the low-fat content in bamboo. In contrast, genes like lipoprotein lipase (LPL), crucial for lipid breakdown, exhibited hypermethylated with low-expression patterns, reflecting a reduced lipid metabolism capacity in adults. Carbohydrate metabolism-related genes like ADH4 and FAM3C are hypomethylated and highly expressed in adults, enhancing glycogen production and glucose utilization. Genes involved in protein metabolism like CTSZ and GLDC, exhibit hypomethylated with high-expression and hypermethylated with low-expression patterns in the pancreas of adults, respectively, contributing to protein metabolism balance post-weaning. Conclusion This study reveals the regulatory role of DNA methylation in the dietary transition of red pandas from milk to bamboo and provides methylation evidence for the molecular regulation of adaptive expression of digestive and metabolic genes in red pandas with specialized diets.